Adaptation of undesirable-output DEA for navigation safety in Taiwan international ports. Issue 1 (1st January 2021) - Wang, Hui-Chiao
Abstract: This study focuses on the impact of the unexpected events of the marine casualties in Taiwan international ports and aims to develop an undesirable-output Data Envelopment Analysis (DEA) model to evaluate navigation safety and acquires the improvement in marine casualties that affect the performance of port safety. Moreover, the major difficulties in this study are the data collection and classification for each marine casualties, the selection of key parameters and weighted value for assessment model. Then, the undesirable-output DEA can conquer the dilemma and render marine casualties be negative factor. This paper searches the main cause about marine casualties adopted by R.O.C. Ministry of Transportation and Communications (MOTC). Based upon 899 sets of marine casualties collected from 2010 to 2019 in Taiwan international ports water, an assessment model comprising four international ports is built, each of which is composed of an input variable and eleven undesirable-output variables. Finally, the results show that: (1) The method which was demonstrated on Taiwan international ports indicates navigation safety ordering is Hualien port, Keelung port, Taichung port and Kaohsiung port. (2) All of the marine casualties, collision and structural damage/ship sinking are the severest casualty that should be improved. Furthermore, the findings of this study correspond to reality so it can help the port authority to take effective risk control actions to increase the navigation safety of international ports.